Mixed‐Methods Pilot Study to Assess Perceptions of Antimicrobial Stewardship in Nursing Homes. Issue 5 (2nd February 2017) - Carter, Rebecca R.; Montpetite, Michelle M.; Jump, Robin L. P.
Abstract : Objectives: To identify features of community nursing home (NH) environments associated with lower rates of overall antibiotic use. Design: This pilot study used an explanatory sequential design that incorporated comparative feedback about antibiotic use to inform a discussion about antimicrobial stewardship practices in community NHs. Setting: NHs. Participants: Clinical leadership of five NHs. Measurements: For the quantitative phase, the number of antibiotic prescriptions, length of therapy, and days of therapy/1, 000 days of care were measured at six NHs. For the qualitative phase, semistructured interviews were conducted with healthcare workers in leadership positions at five community NHs. Transcripts from the recorded interviews were assessed using emergent thematic analysis. For the triangulation phase, themes from the semistructured interviews were evaluated in the context of each NH's antibiotic use. Results: The number of antibiotic prescriptions ranged from 172 to 1, 244, with 50% to 83% written for 7 days or fewer. All NHs reported a similar proportion of fluoroquinolone use (27–32% of days of therapy). Triangulation yielded six themes for which the environment at each facility ranged from less‐ to more‐supportive antimicrobial stewardship: practice patterns, external influences, infection control, leadership, communication, and facility culture. All NHs reported pressure from well‐intentioned family members to prescribe antibiotics. NHs with shorter lengths of therapy and lower overall antibiotic use were consonant with an environment more supportive of antimicrobial stewardship. Conclusion: These findings suggest several features of NHs that are supportive of antimicrobial stewardship: practice patterns grounded in established diagnostic criteria, proactive infection control and prevention, open communication and interconnectedness among staff.